2020
DOI: 10.1681/asn.2019080811
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Clearance of Secretory Solutes Is Associated with Progression of CKD: The CRIC Study

Abstract: BackgroundThe secretion of organic solutes by the proximal tubules is an essential intrinsic kidney function. However, the clinical significance of the kidney’s clearance of tubular secretory solutes is uncertain.MethodsIn this prospective cohort study, we evaluated 3416 participants with CKD from the Chronic Renal Insufficiency Cohort (CRIC) study. We measured plasma and 24-hour urine concentrations of endogenous candidate secretory solutes at baseline, using targeted liquid chromatography–tandem mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 44 publications
3
64
0
Order By: Relevance
“…However, almost half of the patients had diabetes, which is known to have a significant impact not only on the progression of CKD but also on the serum levels of uremic toxins [ 23 ]. Recently, it has been shown that lower kidney clearance of six endogenous solutes, including IS, but not pCS, are associated with a higher risk of CKD progression in adults participating in the CRIC study [ 24 ], which is in line with our results. In our study we provide the first results about the association of IS with progression of CKD in pediatric patients who had no other comorbidities which might interfere with renal survival.…”
Section: Discussionsupporting
confidence: 92%
“…However, almost half of the patients had diabetes, which is known to have a significant impact not only on the progression of CKD but also on the serum levels of uremic toxins [ 23 ]. Recently, it has been shown that lower kidney clearance of six endogenous solutes, including IS, but not pCS, are associated with a higher risk of CKD progression in adults participating in the CRIC study [ 24 ], which is in line with our results. In our study we provide the first results about the association of IS with progression of CKD in pediatric patients who had no other comorbidities which might interfere with renal survival.…”
Section: Discussionsupporting
confidence: 92%
“…In renal dysfunction, the tubular cells develop several disturbances of metabolism and molecular transport as well as of inflammatory reactions detectable in blood circulation that are reflected only partially by serum creatinine [ 28 , 48 ]. Accordingly, tubular clearances of secretory solutes were suggested to provide complementary information about kidney health beyond measurements of glomerular function alone [ 49 ]. Thus, the pathogenesis of renal dysfunction can be considered a complex multi-factorial series of molecular events associated with alterations of various disease pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Serum kynurenic acid, p-cresol sulfate and indoxyl sulfate concentrations were quantified by LC-MS/MS using previously published methods (13). Samples were precipitated in organic solvent, followed by solid phase extraction (Phree phospholipid removal plate).…”
Section: Metabolite Quantificationmentioning
confidence: 99%
“…It is postulated that this endotoxemia stimulates innate immune responses and proinflammatory pathways that contribute to excess cardiovascular pathology in this population. Moreover, a variety of gut-derived bacterial metabolites with purported cardiovascular toxicity accumulate in the circulation of patients with CKD (9)(10)(11)(12)(13)(14). Pcresol sulfate, indoxyl sulfate and trimethylamine N-oxide (TMAO) are well-established examples of such metabolites (9).…”
Section: Introductionmentioning
confidence: 99%